Dragon Quest monsters+. 1 - Yoshizaki, Mine; King, Danielle (Seven Seas Entertainment, 2019)
When the king asks Kleo to train monsters to fight against the forces of darkness, he sets out on a journey to find some potential trainees with only one sassy slime to back him up.